The quality of life concept corresponds with the Islamic philosophy - Zain, Osman Md. (2010)
This paper discusses the quality of life marketing and the societal marketing from the perspectives of the Islamic philosophy. Each of the four P’s of marketing are discuss one by one, though not that through, while comparing it with guidelines and advices from the Quraan and the AlHadiths. With the intention as the beginnings of all marketing activities, the marketing practices can be considered as Islamic if that intention is in the name of ALLAH, and seeks the blessings from ALLAH. This also corresponds to the essence of the religion of Islam that is “way of life”. The products and services are produced for the consumers in the name of ALLAH, and the production of those products and services are strictly adhered to the guidelines from the Islamic philosophy based on the Quraan and AlHadith. Thus, the Quality of life marketing is technically different from the societal marketing.